Comparison of three ionic liquids pretreatment of Arundo donax L. For enhanced photo-fermentative hydrogen production. (January 2022) - Chen, Zhou; Jiang, Danping; Zhang, Tian; Lei, Tingzhou; Zhang, Huan; Yang, Jiabin; Shui, Xuenan; Li, Fang; Zhang, Yang; Zhang, Quanguo
Highlights: Three ILs pretreatment of Arundo donax L. were compared. [Bmim]HSO4 pretreatment obtained relative higher delignification. 16 g/L [Bmim]HSO4 pretreatment enhanced the hydrogen yield by 35.3%. Saccharification of feedstock played a key role in hydrogen production. Abstract: Ionic liquids (ILs) pretreatment has been regarded as a promising green way to treat lignocellulosic biomass. 1-Butyl-3-methylimidazolium tetrafluoroborate ([Bmim]BF4 ), 1-allyl-3-methylimidazolium chloride ([Amim]Cl), and 1-Butyl-3-methylimidazolium Hydrogen Sulfate ([Bmim]HSO4 ) with different loadings (2, 4, 8, and 16 g/L) were adopted to pretreat the Arundo donax L.. 16 g/L [Bmim]HSO4 pretreated Arundo donax L. obtained the highest sugar yield of 7.9 g/L during the enzymatic hydrolysis and hydrogen yield of 106.1 mL/g TS during the photo-fermentation, which were 68.8 % and 35.3 % higher than those of untreated Arundo donax L., respectively. Moreover, volatile fatty acids (VFAs) distribution revealed that acetic acid was the main by-product during hydrogen production process with ILs pretreated Arundo donax L.. Besides, the relationship between sugar yield and hydrogen yield was the closest based on scatter matrix analysis. This study helps to understand of correlation between ILs pretreatment with the behavior of bioenergy production.